Comparative effects of foliar biogenic selenium nanoparticles and selenite on soybean growth, seed quality, selenium speciation and bioaccessibility - Ssemalawa, Solomon Musoke; Asamoah, Emmanuel Osei; Farooq, Muhammad Raza; Bañuelos, Gary; Wang, Yuanqi; Sun, Haoyuan; Rao, Pincheng; Guo, Yukun; Chen, Youtao; Yin, Xuebin (Frontiers in Plant Science, 2025)
Selenium (Se) biofortification of crops presents a sustainable strategy to address Se deficiency, which globally affects nearly one billion people. Although selenite [Se(IV)] fertilizers are commonly used for biofortification strategies, concerns over their potential toxicity in plants and low bioaccessibility have prompted interest in alternative Se sources, such as biogenic Se nanoparticles (BSeNPs). A field study was conducted to explore the effects of foliar BSeNPs and Se(IV) at 5, 10, and 20 mg L-¹ on soybean growth, nutritional quality, Se speciation, and bioaccessibility. Application of BSeNPs at 5 mg L-¹ enhanced shoot biomass (54.2%), seed protein content (62.3%), and total amino acids (76.2%) compared to both the control and corresponding Se(IV) treatments. Enhanced antioxidant enzyme responses (SOD, POD) and a decline in lipid peroxidation (MDA) were also observed with BSeNPs application, indicating enhanced stress tolerance. While Se(IV) led to higher total Se accumulation, BSeNPs promoted greater enrichment of organic Se species (SeMet, SeCys, MeSeCys). In vitro digestion showed that total bioaccessible Se (gastric + intestinal) ranged from 45-56% for BSeNPs versus 19.6-34% for Se(IV). In conclusion, these findings indicate that foliar BSeNPs at 5–10 mg L-¹ were more effective than Se(IV) for improving seed nutritional quality and Se bioaccessibility in soybean biofortification.